Traces of Guilt and a Hint of Reparation in Kyung-Sook Shin’s Please Look After Mother - Das, Shruti; Adak, Suman (Literary Studies, 2024)
Guilt arises with the realization of wrongdoing. Please Look After Mother by noted South Korean writer Kyung-Sook Shin is replete with repentance which finds perfect expression in the characters' memories. Like in most oriental societies family and emotional and physical relationships between family members are very important and the basis of stability. Failing to care for members of one’s family is considered sacrilege and looked down upon. Therefore, neglect of family results in guilt. In the novel, the mother goes missing from the Railway station and the other family members blame each other and themselves in high drama. The characters, not only exhibit guilt but also are aware of their own guilt. The narrative exposes the human psyche projecting how unconscious guilt often manifests itself if the stakes are as high as losing suddenly one’s mother and wife. The guilt emerges and the ‘feeling bad’ turns eventually into a creative expression of prayer. This paper is a psychoanalytic study of Please Look After Mother whereby the emotional bond in a family is explored. This paper aims to fill the need for a comprehensive psychoanalytic study when it comes to the guilt the characters feel while putting forth the idea of family as a bounded structure and its reparation from the novel itself.